Baroness Charlotta Castelli Glembay - was she hypersexual? : Barunica Charlotta Castelli Glembay - je li ona bila hiperseksualna? - Arbanas, Goran (Array, 2021)
Hypersexuality disorder (or sexual addiction or excessive sexual drive or compulsive sexual behaviour disorder) is a controversial condition that is present in the International Classification of Disease but not in the Diagnostic and Statistical Manual for Mental Disorders. It is defined as a clinical syndrome characterised by a persistent pattern of failure to control intense, repetitive sexual impulses or urges resulting in repetitive sexual behaviour. The condition is more prevalent in men than in women. Some medical conditions were described in fictional literature before their formal recognition in medicine, like Huntington disease, Pickwick syndrome, and Munchausen syndrome. The aim of this article is to analyse the fictional character of Charlotta Castelli Glembay from Miroslav Krleža"s play Messrs Glembays from 1928. Krleža presented a woman with a sexual drive that could be described as uncontrollable, organic (physical) in origin, and different from love and affection (that she also experienced, but only with one particular man). The author gave a special name for her condition – erotic intelligence. This sexual behaviour has distressing and devastating consequences. This paper will argue that the play depicts hypersexuality disorder in a woman, with a designation of its aetiology. In concordance with the prevailing attitudes of the time (the early 20th century), hypersexuality in women had negative attributions.